New Insights into the Structural Requirements of Isatin-Derived Pro-Apoptotic Agents against Acute Myeloid Leukemia - Ahmed K. Hamdy; Takashi Sakamoto; Tsugumasa Toma; Masaharu Sakamoto; Mohammed A. S. Abourehab; Masami Otsuka; Mikako Fujita; Hiroshi Tateishi; Mohamed O. Radwan (MDPI AG, 2022)
Searching for bioactive compounds within the huge chemical space is like trying to find a needle in a haystack. Isatin is a unique natural compound which is endowed with different bio-pertinent activities, especially in cancer therapy. Herein, we envisaged that adopting a hybrid strategy of isatin and α,β-unsaturated ketone would afford new chemical entities with strong chemotherapeutic potential. Of interest, compounds 5b and 5g demonstrated significant antiproliferative activities against different cancer genotypes according to NCI-60 screening. Concomitantly, their IC50 against HL-60 cells were 0.38 ± 0.08 and 0.57 ± 0.05 µM, respectively, demonstrating remarkable apoptosis and moderate cell cycle arrest at G1 phase. Intriguingly, an impressive safety profile for 5b was reflected by a 37.2 times selectivity against HL-60 over PBMC from a healthy donor. This provoked us to further explore their mechanism of action by in vitro and in silico tools. Conclusively, 5b and 5g stand out as strong chemotherapeutic agents that hold clinical promise against acute myeloid leukemia.